(untitled) (Baghdad Science Journal, 2016)
The parasite tapeworm (Raillietina echinobothrida) belonges to the class Cestoda, it is responsible for nodular tapeworm disease in poultry .The aim of this study was to determine tapeworm parasites infections in Columba livia from two markets in the province of Baghdad for the period from May to December 2014. From a total of thirty five sample of Columba livia were randomly selected and then examined the elementary canal of these samples. The present study showed that the collected rock pigeon were found six infected with the cestode Raillietina echinobothrida with infection rate (17.14%). The statistical analysis for the characters of the cestode showed significant differences in all recipes, but there were no significant differences in the length character of rostellum hooks.